PENGARUH KOMUNIKASI TENTANG IJIN MENDIRIKAN BANGUNAN (IMB) OLEH KANTOR PELAYANAN PERIJINAN TERPADU (KPPT) TERHADAP PARTISIPASI MASYARAKAT DALAM PENGURUSAN PEMBUATAN IJIN MENDIRIKAN BANGUNAN (IMB) DI KOTA CIREBON - Didi Saputra; Heriyani Agustina; Mukarto Siswoyo (Universitas Swadaya Gunung Jati, 2013)
Research by the author is the influence of communication on building permit (IMB) by unifiedlicensing offices (KPPT) for community participation in the management of the manufactureof building permit (IMB) in the city of Cirebon. The problem is that the writer suggestedparticipation in the manufacture of building permit (IMB) in the city of Cirebon less thanoptimal, the problem is suspected in non optimal result from the implementation of thecommunication by the unified licensing offices (KPPT) Cirebon. The research questionajuakan writer is, is there any influence by the office of the communication servicesintegrated permitting (KPPT) for community participation in the management ofmanufacturing IMB The method I used is quantitative (survey) The hypothesis that theauthors propose is as follows.